1990
DOI: 10.3109/00048679009077681
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Mania in New Zealand

Abstract: This paper examines the seasonal variation in manic admissions over a five year period in New Zealand. There is a significant monthly variation in admission rates with a spring/summer peak. Breakdown by sex, age and admission status suggested that there is no particular subgroup responsible, but that young first admissions and older female readmissions do not follow this trend. Examination of the monthly admission rates revealed that this peak is not constant from year to year. Possible mechanisms, which link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…Similar data had been described by Symond and Williams [2], though these data statistically reanalyzed also showed evidence of such a sea- Kerr-Corrêa/Souza/Calil sonal manic peak for males [26]. However, other studies reported on data indicating that the seasonal admission pattern for mania was more robust in females [10,12]. Despite the limited available data, the possibility of females being more vulnerable than males to the effects of seasonal changes on the course of affective illness, and especially in the recurrent pattern of mania, deserves further research.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Similar data had been described by Symond and Williams [2], though these data statistically reanalyzed also showed evidence of such a sea- Kerr-Corrêa/Souza/Calil sonal manic peak for males [26]. However, other studies reported on data indicating that the seasonal admission pattern for mania was more robust in females [10,12]. Despite the limited available data, the possibility of females being more vulnerable than males to the effects of seasonal changes on the course of affective illness, and especially in the recurrent pattern of mania, deserves further research.…”
Section: Discussionmentioning
confidence: 42%
“…Kerr-Corrêa/Souza/Calil [12]. However, these mania admission peaks have been unstable from year to year [10][11][12], change with age and number of hospital admissions [10], and also show variations in different regions of the same country [11]. In addition, other investigations, carried out in both hemispheres, have not found a seasonal pattern in admission rates for mania [7,8,13,14], nor in manic episodes in a cohort of 86 patients over a 6-year period [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from studies in the southern hemisphere shows similar trends for an increase in mania in the springsummer (30)(31)(32)(33); however, this finding is not universal (34). One finding shows a spring/ summer peak in the depressive phase of the illness (2), whereas others indicate autumn increases (35) or no seasonal variation in depression (34).…”
Section: Introductionmentioning
confidence: 81%
“…Many authors have reported a characteristic trend towards mania during summer months for some patients (Hare and Walter [62] , Myers and Davies [63] and Takei et al [64] ), whilst others report peaks in the spring (Parker and Walter [65] and Mulder et al [66] ). Leuthold [67] , Frangos et al [68] , Carney et al [69] and Kamo et al [70] reported major peaks in the spring and minor peaks in the fall, while McCartney [71] reported a higher frequency in the fall.…”
Section: Seasonal Patternmentioning
confidence: 99%